PELATIHAN PEMBUATAN PUPUK ORGANIK CAIR DARI LIMBAH GEDEBOG PISANG DI DESA BANGKILING - Muhammad Ridho Putra Perdana; Novi Alisa; Fathul Jannah; Siti Nurazizah; Rusmadi Rusmadi; Mutiah Mutiah; Martin Jeremia; Siti Raihanah; Harlina Kusuma Tuti (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Universitas Pattimura, 2026)
Banana pseudostem waste in Bangkiling Village, Banua Lawas District, Tabalong Regency, remains underutilized and is generally left to decompose after harvest. This community service program aimed to improve community knowledge and skills in processing banana pseudostem waste into liquid organic fertilizer (LOF) as an environmentally friendly alternative fertilizer. The activity was conducted on November 8, 2025, involving 15 farmers through counseling sessions, interactive discussions, and hands-on training in LOF production. Evaluation was carried out descriptively through observations of participant attendance, engagement in discussions, and their ability to perform the stages of LOF preparation. The results showed that 100% of participants attended and completed all training activities and were able to practice each stage of LOF production, from material preparation to the fermentation process. Participants were also able to explain the procedures for producing and applying LOF after the training. The program increased participants’ understanding of agricultural waste utilization and encouraged a shift in perception toward banana pseudostem waste, transforming it from a valueless by-product into a useful agricultural resource. Furthermore, participants demonstrated motivation to independently adopt LOF production technology as a means of reducing dependence on chemical fertilizers. Overall, the program proved effective in enhancing community capacity and supporting sustainable agriculture based on locally available resources.